Potato Festival (A Study of Thanksgiving in Modoinding Village Communities, Modoinding District) - Salem, Veronika E.T.; Kumakau, Grasela; Kerebungu, Ferdinand; Mesra, Romi; Sidik, Sangputri (Technium Social Sciences Journal, 2023)
The purpose of this research is to find out and describe the role of the community in celebrating the potato festival in the activities of giving thanksgiving in the village of Wulurmaatus, Modoinding sub-district. The method used in this research is descriptive qualitative method. As for the method of data collection carried out in this study is through interviews, observation, and documentation studies. The data analysis technique used by the author in writing this scientific work is to use the Miles and Huberman model analysis, namely data reduction, data presentation, and drawing conclusions. The results showed that the role of the government as an information medium in conveying also outreach to the general public about the activities of this festival, the religious leaders had a role to carry out a series of events in which thanksgiving there were praise and prayers were said while community leaders and the Wulurmaatus village community started from preparation to with its implementation, it has divided tasks starting from entertaining guests and preparing accommodation and other matters related to this activity.